The diagnostic and therapeutic potential of miR-3149 in osteoporotic fractures through SMAD4 - Guanwei Xu; Zhichao Yang; Sibao Zeng; Yongqi Dong; Lina Huang (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoporotic fractures (OPF) are one of the most common bone diseases in aging societies. MiR-3149 is a short non-coding RNA, its expression level, therapeutic effects, and mechanisms in OPF remain unclear. Purpose This study aims to explore the impact of miR-3149 on OPF progression and uncover its mechanism for influencing OPF progression via SMAD4. Methods In this study, we first used reverse transcription-quantitative polymerase chain reaction (RT-qPCR) to detect miR-3149 expression levels in the serum of OPF patients. Then, we assessed miR-3149’s diagnostic value for OPF via ROC curve analysis. Using cell counting kit-8 (CCK-8) assays, flow cytometry, and RT-qPCR, we explored miR-3149’s effects on cell proliferation, apoptosis, and the expression of key factors RANK and NFATc1. Furthermore, we examined SMAD4 expression in RAW264.7 cells and conducted a dual-luciferase reporter assay to confirm the interaction between miR-3149 and SMAD4. Finally, we analyzed how miR-3149 regulates SMAD4 expression and investigated the effects of miR-3149-mediated SMAD4 regulation on cell function. Results This study reveals that miR-3149 is markedly upregulated in the OPF group, effectively differentiating the control and case groups. MiR-3149 knockdown suppressed RAW264.7 cell proliferation and osteoclastic differentiation, while inducing apoptosis. Notably, SMAD4, a downstream target gene of miR-3149, was low-expressed in RANKL-induced RAW264.7 cells, and exhibits specific binding with miR-3149. Co-transfection with pcDNA-SMAD4 reversed the effects of mimic-miR on RAW264.7 cell proliferation, apoptosis, and osteoclastic induction. Conclusions Down-regulating miR-3149 inhibited the osteoclastic generation ability of RAW264.7 by up-regulating SMAD4 expression.